Anatomical spatial-temporal distribution and multivariate risk of acute injuries in elite rugby: a cohort based on prospective surveillance - Chen, Z.; Wang, X.; Mei, X. (Frontiers in Physiology, 2026)
Background: Acute injuries are common in rugby and threaten both player health and career longevity. Previous studies often focused on isolated risk factors, while limited research has comprehensively examined the interplay of physiological, environmental, and situational variables.